PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PUZZLE TERHADAP HASIL BELAJAR MATEMATIKA MATERI PEMBAGIAN SISWA KELAS IV DI SEKOLAH DASAR - Tiara Azzahra; Nurul Febrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by teacher-centered learning which results in low mathematics learning outcomes and students' lack of active participation. This research aims to determine the use of puzzle learning media on the mathematics learning outcomes of class IV students in elementary school. This research uses a quantitative approach with a one group pretest-posttest type pre-experimental design. The population of this study involved 32 students in class IV-B and the research sampling technique was purposive sampling. Techniques used to collect data include tests, questionnaires and documentation. The results of the research obtained through the t-test showed rcount 10,345 > rtable 2,040 and sig (2-tailed) value 0.001<0.05. It can be stated that Ho is rejected and Ha is accepted, meaning that there is an influence between the use of puzzle learning media on mathematics learning outcomes.